2021
DOI: 10.1001/jamanetworkopen.2021.16420
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Multisystem Inflammatory Syndrome in Children Among US Persons Infected With SARS-CoV-2

Abstract: IMPORTANCE Multisystem inflammatory syndrome in children (MIS-C) is associated with recent or current SARS-CoV-2 infection. Information on MIS-C incidence is limited. OBJECTIVE To estimate population-based MIS-C incidence per 1 000 000 person-months and to estimate MIS-C incidence per 1 000 000 SARS-CoV-2 infections in persons younger than 21 years. DESIGN, SETTING, AND PARTICIPANTS This cohort study used enhanced surveillance data to identify persons with MIS-C during April to June 2020, in 7 jurisdictions re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
256
5
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 314 publications
(303 citation statements)
references
References 22 publications
14
256
5
4
Order By: Relevance
“…A recent systematic review found that 31–62% of persons with MIS-C were of Black or Afro-Caribbean race and 36–39% were Hispanic or Latino [ 14 ]. Even after accounting for the increased burden of COVID-19, the incidence of MIS-C is higher among Black and Hispanic or Latino persons compared to White persons [ 15 ].…”
Section: Multisystem Inflammatory Syndrome In Childrenmentioning
confidence: 99%
“…A recent systematic review found that 31–62% of persons with MIS-C were of Black or Afro-Caribbean race and 36–39% were Hispanic or Latino [ 14 ]. Even after accounting for the increased burden of COVID-19, the incidence of MIS-C is higher among Black and Hispanic or Latino persons compared to White persons [ 15 ].…”
Section: Multisystem Inflammatory Syndrome In Childrenmentioning
confidence: 99%
“…Among males aged ≥30 years, 15,300 COVID-19 cases, 4,598 hospitalizations, 1,242 ICU admissions, and 700 deaths could be prevented, compared with three to four expected myocarditis cases after COVID-19 vaccination. This analysis did not include the potential benefit of preventing post-COVID-19 conditions, such as prolonged symptoms and MIS-C ( 6 , 7 ).…”
mentioning
confidence: 99%
“…[36][37][38][39][40][41] A recent population-based study in the US estimated the rate of MIS-C at 1 in 3,100 SARS-CoV-2 infections in persons younger than 21 years. 42 44 Furthermore, a large cohort study of children in the United Kingdom found that only 1.8% of children had one or more residual symptoms (compared to 0.9% of SARS-CoV-2 negative controls) two months after their acute illness. 45 Ongoing research into longer-term morbidities in children after SARS-CoV-2 infection is warranted, though findings so far are reassuring.…”
Section: Covid-19 Disease In Children and Youthmentioning
confidence: 99%